2011
DOI: 10.1016/j.biomaterials.2011.01.057
|View full text |Cite
|
Sign up to set email alerts
|

An overview of tissue and whole organ decellularization processes

Abstract: Biologic scaffold materials composed of extracellular matrix (ECM) are typically derived by processes that involve decellularization of tissues or organs. Preservation of the complex composition and three-dimensional ultrastructure of the ECM is highly desirable but it is recognized that all methods of decellularization result in disruption of the architecture and potential loss of surface structure and composition. Physical methods and chemical and biologic agents are used in combination to lyse cells, follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

85
3,225
7
77

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 2,929 publications
(3,394 citation statements)
references
References 118 publications
(238 reference statements)
85
3,225
7
77
Order By: Relevance
“…Intact and fragmented DNA has the potential to elicit an inflammatory response, which can lead to rejection of the graft in vivo. Crapo et al (2011) have proposed a decellularised graft should have less than 50 ng double stranded DNA per mg ECM dry weight as well as lack of visible nuclear material in tissue sections, which can be determined using DAPI or by H&E staining.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intact and fragmented DNA has the potential to elicit an inflammatory response, which can lead to rejection of the graft in vivo. Crapo et al (2011) have proposed a decellularised graft should have less than 50 ng double stranded DNA per mg ECM dry weight as well as lack of visible nuclear material in tissue sections, which can be determined using DAPI or by H&E staining.…”
Section: Resultsmentioning
confidence: 99%
“…These treatments are used to solubilise both cytoplasmic proteins and nuclear cellular membranes. Additional enzymatic treatments such as nucleases are added for the removal of the cellular debris (Crapo et al, 2011; Gilbert et al, 2006). During the decellularisation process proteases are released from lysed cells, which can cause damage to the native ECM ultrastructure.…”
Section: Introductionmentioning
confidence: 99%
“…SDS is an ionic detergent and has been reported to decellularize organs fully 3, 4. POETE, in contrast, belongs to the class of nonionic detergents and is ineffective at stripping tissue of cellular material.…”
Section: Resultsmentioning
confidence: 99%
“…The Badylak group (Crapo et al ., 2011) have suggested criteria (DNA content and lack of visible nuclear material in tissue sections stained with H&E or DAPI) by which a tissue can be judged decellularized based upon studies in which an in vivo constructive remodelling response has been observed. Following decellularization, no evidence of cells, cellular remnants or nuclear material were present in histological sections of the aortic or pulmonary valve tissues and there was no evidence of overt damage to the ECM, as judged by low‐resolution light microscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that these decellularized human donor cardiac valves have been implanted into patients now for several years, details of the DNA levels in these decellularized human donor valve allografts is lacking. This is surprising given that DNA levels are a good indicator of the degree of cell removal (Crapo et al ., 2011) and the potential role of residual cellular DNA in calcification of tissue heart valve substitutes (Schoen and Levy, 2005). To our knowledge this is first report of a decellularization process that removes over 97% of the DNA from the junctional region of human aortic and pulmonary valve conduits.…”
Section: Discussionmentioning
confidence: 99%